Allogeneic platelet‐rich plasma affects monocyte differentiation to dendritic cells causing an anti‐inflammatory microenvironment, putatively fostering wound healing. (11th May 2017) - Papait, Andrea; Cancedda, Ranieri; Mastrogiacomo, Maddalena; Poggi, Alessandro
Abstract: Autologous platelet‐rich plasma (PRP) is used clinically to induce repair of different tissues through the release of bioactive molecules. In some patients, the production of efficient autologous PRP is unfeasible due to their compromised health. Allogeneic PRP mismatched for AB0 and Rh antigens was developed. The effect of allogeneic PRP on immune response should be defined to use it in clinical practice avoiding side effects. Thus, whether PRP affects the differentiation of peripheral blood monocytes to dendritic cells upon stimulation with granulocyte monocyte colony stimulating factor and interleukin‐4 was investigated. Indeed, these cells are the main players of immune response and tissue repair. PRP inhibited the differentiation of monocytes to CD1a + dendritic cells and favoured the expansion of phagocytic CD163 + CD206 + fibrocyte‐like cells. These cells produced interleukin‐10 and prostaglandin‐E2, but not interferon‐γ, upon stimulation with lipopolysaccharides. Moreover, they promoted the expansion of regulatory CD4 + CD25 + FoxP3 + T cells upon allostimulation or antigen specific priming. Finally, the conditioned medium harvested from monocytes differentiated with PRP triggered a strong chemotactic effect on mesenchymal cells in both scratch and transwell migration assays. These results strongly suggest that allogeneic PRP can foster the differentiation of monocytes to a regulatory anti‐inflammatory population, possibly favouring wound healing. Copyright © 2016 John Wiley & Sons, Ltd. Abstract :